2019
DOI: 10.28955/alinterizbd.639020
|View full text |Cite
|
Sign up to set email alerts
|

The Variability of the Predominant Culturable Plant Growth-Promoting Rhizobacterial Diversity in the Acidic Tea Rhizosphere Soils in the Eastern Black Sea Region

Abstract: The purpose of this study was to investigate the diversity of cultivable nitrogen fixing, phosphate solubilising and total bacteria originated from 580 rhizospheric acidic soils samples of tea plants grown at 62 locations. Based on FAME profiles of over 1428 rhizoplane bacteria, 63 bacterial genera were identified with a similarity index > 0.3, but 56.4% of the identified isolates belonged to six genera: Bacillus (37.02%), Pseudomonas (12.67%), Stenotrophomonas (5.71%), Paenibacillus (6.58%), Arthrobacter (4.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…However, only a few reports are available focusing on the PPFMs in the tea ecosystem. Chinese researchers, Xie et al, (2020) and Cakmakci (2019) reported the isolation a p p r o a c h e s a n d t h e d i s t r i b u t i o n o f Methylobacterium in the acidic tea rhizosphere soil. In North India, Bora et al, (2021)…”
Section: Resultsmentioning
confidence: 99%
“…However, only a few reports are available focusing on the PPFMs in the tea ecosystem. Chinese researchers, Xie et al, (2020) and Cakmakci (2019) reported the isolation a p p r o a c h e s a n d t h e d i s t r i b u t i o n o f Methylobacterium in the acidic tea rhizosphere soil. In North India, Bora et al, (2021)…”
Section: Resultsmentioning
confidence: 99%
“…Further research shows that tea rhizosphere bacterial communities are often enriched with members of Proteobacteria , Firmicutes , and Acidobacteria , accounting for 67.81% of total rhizosphere bacteria. At the same time, Proteobacteria , Acidobacteria , and Chloroflexi were the main phyla in the tea bulk soil and accounted for 60.00% of total bulk soil bacteria (Figure a). Nevertheless, the most abundant bacterial phyla in the tea rhizosphere soil were Firmicutes (with Bacillus and Lysinibacillus genera representing over 82.00%), which was about 2-fold or higher in the relative abundance in the tea rhizosphere soil (24.06%) than that in the bulk soil (9.31%). Simultaneously, Verrucomicrobia was more abundant in the tea rhizosphere soil (5.34%) than in the bulk tea soil (2.73%). In contrast, Chloroflexi was enriched in the bulk soil (accounting for 11.05%), which was more than one-fold abundance in the bulk soil compared with that in the tea rhizosphere soil.…”
Section: Diversity Of Rhizosphere Microorganism In Tea Plantmentioning
confidence: 95%
“…136 Besides, the rhizosphere bacteria belonging to genera Bacillus, Pseudomonas, Stenotrophomonas, Arthrobacter, and Serratia were the most frequent N-fixing bacteria in the tea rhizosphere soils. 25,137,138 Notably, for tea productivity, Azosprillum is the most efficient for increasing the N nutrient enhancement, which stimulates the density and length of tea plant root hairs through fixed nitrogen to absorb nutrition and increases tea plant biomass and survival rate. 139 Rhizosphere microorganisms can collectively maintain the content of soil-absorbable nitrogen compounds and improve the yield of tea plants by participating in nitrogen fixation.…”
Section: Increase Resilience To Extremementioning
confidence: 99%
See 1 more Smart Citation